Environmental education and education for sustainable development: Conceptual solutions and dilemmas - Orlović-Lovren Violeta (Nastava i Vaspitanje, 2021)
The focus on education for sustainable development in global policy and literature opens up a range of different views on its relationship with environmental education. While a number of authors make a clear distinction between the two concepts, others believe that education for sustainable development (ESD) has actually displaced environmental education (EE). Different perceptions of these two concepts have implications for their integration into education at all levels. This paper offers a comparative analysis of trends and directions in defining these concepts both in global policy documents and in the literature in this field, with the aim of offering another perspective on their relationship and on the possibility of implementation in practice. The overview of the similarities and differences in their coneptualization has prompted a reconsideration of the dilemmas regarding the need for the existence of both concepts and the possibility of integrating them into education, which should play a key role in the achievement of the ideal of sustainability